Prevalence of respiratory viruses in community-acquired pneumonia in children: a systematic review and meta-analysis. (August 2022) - Pratt, Mitchell T G; Abdalla, Tasnim; Richmond, Peter C; Moore, Hannah C; Snelling, Thomas L; Blyth, Christopher C; Bhuiyan, Mejbah U
Summary: Background: Respiratory viruses are increasingly detected in children with community-acquired pneumonia but prevalence estimates vary substantially. We aimed to systematically review and pool estimates for 22 viruses commonly associated with community-acquired pneumonia. Methods: We conducted a systematic review and meta-analysis to determine the prevalence of each of the common respiratory viruses detected by any diagnostic method in children aged up to 18 years with community-acquired pneumonia. We searched MEDLINE, PubMed, Embase, Web of Science, and Scopus databases with no language restrictions for relevant published articles and reports published between Jan 1, 1995, and Dec 31, 2019, restricting the review to pre-COVID-19 pandemic years. Three independent reviewers screened articles and extracted data using a predefined protocol. We calculated the pooled prevalence for each virus in childhood pneumonia using DerSimonian–Laird random-effects models. We assessed bias using the Newcastle–Ottawa Scale. The review protocol was registered in PROSPERO (CRD42016034047). Findings: We identified 186 eligible articles that represented 152 209 children up to age 18 years with community-acquired pneumonia. One or more respiratory viruses were detected in 55·0% (95% CI 50·4–59·7) of paediatric patients with a diagnosis of community-acquired pneumonia; heterogeneity was high ( I 2 =99·4%). Respiratory syncytial virus (22·7%, 20·9–24·5) and rhinovirus (22·1%, 19·5–24·7) were the most commonly detected causes of paediatric pneumonia globally, with other viruses detected in 1–9% of cases. There was non-significant variation in prevalence by the country's national income, under-5 mortality rate, or WHO region. Interpretation: Respiratory viruses are frequently detected in community-acquired pneumonia among children of all ages and geographical regions, with non-significant variation by country's national income or region. Further strategies to limit antibiotic use in children with viral pneumonia and develop treatment and prevention approaches targeting common respiratory viruses are expected to have a substantial effect on the residual burden of childhood pneumonia. Funding: None.